2015
DOI: 10.1016/j.biocon.2015.02.026
|View full text |Cite
|
Sign up to set email alerts
|

Plantations, not farmlands, cause biotic homogenisation of ground-active beetles in south-eastern Australia

Abstract: a b s t r a c tFollowing landscape change, species invasions and extinctions may lead to biotic homogenisation, resulting in increased taxonomic and functional similarity between previously distinct biotas. Biotic homogenisation is more likely to occur in landscapes where the matrix contrasts strongly with native vegetation patches. To test this, we examined the distribution of ground-active beetles in a landscape of remnant Eucalyptus open woodland patches where large areas of lower contrast matrix (farmland)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 99 publications
(120 reference statements)
1
11
0
Order By: Relevance
“…This is consistent with previous studies at the same site, in which conversion of natural grassland to irrigated cropland or pure poplar and pure pine plantations significantly decreased activity abundance and taxon richness of ground-active arthropod communities Feng et al, 2015). Sweaney et al (2015) also found that replacement of agricultural pastures by pure pine plantations resulted in significantly decreased species richness of ground-active beetle assemblages.…”
Section: Effects Of Shrub Shelterbelts On Beetle Diversity and Communsupporting
confidence: 92%
See 2 more Smart Citations
“…This is consistent with previous studies at the same site, in which conversion of natural grassland to irrigated cropland or pure poplar and pure pine plantations significantly decreased activity abundance and taxon richness of ground-active arthropod communities Feng et al, 2015). Sweaney et al (2015) also found that replacement of agricultural pastures by pure pine plantations resulted in significantly decreased species richness of ground-active beetle assemblages.…”
Section: Effects Of Shrub Shelterbelts On Beetle Diversity and Communsupporting
confidence: 92%
“…Sweaney et al . () also found that replacement of agricultural pastures by pure pine plantations resulted in significantly decreased species richness of ground‐active beetle assemblages.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Li et al (2016) concluded that shrub plantations reduce beetle diversity. Many research illustrated that the main cause of reducing the biodiversity of many terrestrial ecosystem is the changes in the land use/ cover (Garnier et al, 2006;Krauss et al, 2010;Garcia-Tejero et al, 2013;Vergnes et al, 2014;Sweaney et al, 2015). Liu et al (2015) concluded that shrub diversity and season variations are the significant factors for ground beetle assemblages in the desert ecosystem, while the responses of beetles varied among trophic and taxonomic levels.…”
Section: Discussionmentioning
confidence: 99%
“…To assess the similarity of the seeds, we computed Sørensen (Taguas, et al, 2015) and Bray-Curtis indices (Helsen et al, 2015) with Primer 5 (Clarke & Gorley, 2001) and checked their significance using analysis of similarity (ANOSIM) (Sweaney et al, 2015). Analysis of ordination was executed in PC-ord 5.0 (McCune & Mefford, 2005) using DCA (detrended corresponding analysis) to determine the zonation along a water depth gradient.…”
Section: Discussionmentioning
confidence: 99%